Feasibility of Patient-Centric Remote Dried Blood Sampling: The Prediction, Risk, and Evaluation of Major Adverse Cardiac Events (PRE-MACE) Study. (2nd October 2019) - Fuller, Garth; Njune Mouapi, Kelly; Joung, Sandy; Shufelt, Chrisandra; van den Broek, Irene; Lopez, Mayra; dhawan, Shivani; Mastali, Mitra; Spiegel, C; Bairey Merz, Noel; Van Eyk, Jennifer E.; Robinson, Aaron
ABSTRACT: Background : Remote patient monitoring can shift important data collection opportunities to low-cost settings. Here, we evaluate whether the quality of blood-samples taken by patients at home differs from samples taken from the same patients by clinical staff. We examine the effects of socio-demographic and patient reported outcomes (PRO) survey data on remote blood sampling compliance and quality. Methods : Samples were collected both in-clinic by study-staff and remotely by subjects at home. During cataloging the samples were graded for quality. We used chi-squared tests and logistic regressions to examine differences in quality and compliance between samples taken in-clinic versus samples taken by subjects at-home. Results : 64.6% of in-clinic samples and 69.7% of samples collected remotely at home received a Good (compared to Not Good ) quality grade (chi2 = 4.91; p =.03). Regression analysis found remote samples had roughly 1.5 times higher odds of being Good quality compared to samples taken in-clinic ( p <.001; 95% CI 1.18–2.03). Increased anxiety reduced odds of contributing a Good sample ( p =.04; 95% CI.95–1.0). Response rates were significantly higher for in-clinic sampling (95.8% vs 89.8%; p <.001). Conclusion : Blood-samples taken by patients at home using a microsampling device yielded higher quality samples than those taken in-clinic.